Tratamento de sementes de tabaco e seus efeitos imediatos e após armazenamento na qualidade fisiológica e sanitária - Ribeiro, Ana Maria Pereira (2020)
Seed treatment is very important to ensure uniformity and desirable crop stand, mainly in disease control at the beginning of its development. Despite the damage caused by fungi in seedlings, currently in Brazil there are no official or research indications for the treatment of tobacco seeds. To evaluate the immediate effect and after storage of tobacco seed treatment on their physiological quality, we used two seed lots of cultivars CSC 444 and CSC 4703 Virginia group varietal. The seeds were subjected to seed treatment with the fungicides Captana, Tiabendazole, Carboxina + Tiram, sodium hypochlorite, silver nitrate and thermotherapy. Untreated seeds were used as control. The initial characterization of the seed quality of the used lots was carried out and the evaluations were performed soon after the seed treatment and after six months of storage. Seed water content, germination, first germination count, germination and emergency speed index, initial and final emergence, electrical conductivity, cold test, seedling growth and sanitary analysis were determined. The design was completely randomized, in a 7x2x2 factorial scheme (seven treatments, two lots and two storage times) for each cultivar. The treatment effect of tobacco seeds with chemicals for the control of pathogens varies depending on the initial quality of the lots. Thermotherapy at 52 °C for 30min, 0.1% silver nitrate for 20 min, 1% sodium hypochlorite and Tecto® in the dosage of 300 mL/100 kg of seeds negatively affect the quality of tobacco seeds. The treatments with Captan® in the dose of 200 mL / 100 kg of seeds and Vitavax-Thiram® in the dose of 250 mL/ 100 kg of seeds provide superior results of vigor after the six months of storage of tobacco seeds in conditions of 10 °C.